Performance, corpo, limite e acontecimento: um experiência nas artes visuais - Malavolta, Ana Paula Parise (2017)
This research aims to construct a theoretical-critical course about the meaning of the limit of the artist's body in performance through the experiences of the artist Rafael Falk. In order to do so, the concepts of body, limit and event in front of references of Art and of Philosophy are problematized, seeking to approach the present concepts with the process of mapping the face-to-face performances performed by this young artist. In the theoretical basis of this study, we use the Philosophy of Gilles Deleuze and Baruch de Espinosa, approaching references and concepts that are interconnected and related to the research topic, inserted in the field of Visual Arts. The artists who construct the references of this study are Joseph Beuys, Marina Abramovic, Regina Jose Galindo and Rafael Falk. The methodology of this research is characterized by Cartography, which presents itself as a practice of experiences of ongoing processes and flows that, rather than tracing historical paths, occupy itself with a field of forces within the same territories , Be they the field and / or the practice, or the theory. Thus, we can understand that the limit of the body experienced in performance by Rafael Falk seems to unfold by a certain transgression to produce a unique encounter of the artist with his body, impelling it to construct new poetic actions. We consider that the production of affects between bodies (artist and public), constitutes in time and space of performance, what we understand as a whole body. This whole body is produced by processes of relations between the elements of performance in the present moment (here and now), which characterizes that the performance actions have their composition as an event.